Hubungan Pola Asuh Orang Tua dan Gender terhadap Kemandirian Anak Usia Dini PAUD Pertiwi Kutacane - Sutri Nazrah; Sri Milfayetty; M Rajab Lubis (Mahesa Research Center, 2022)
The purpose of this study was to determine the effect of parenting and gender on AUD independence. This research method uses quantitative methods. The population of this study was 75 people and a sample of 75 people, the researchers used a total sampling technique. The results showed that there was a significant correlation between parenting on independence seen from the coefficient value (r2) which had a value of 0.633 with p or significance 0.000 < 0.050 with the correlation of parenting to independence of 63.3%. Furthermore, it is known that there is a significant influence between gender on independence as seen from the coefficient value (R2) which has a value of 0.038 with p or a significance of 0.006 < 0.050, with the contribution of gender to independence only 3.8%. Simultaneously there is a significant effect between parenting and gender on independence as seen from the coefficient value (R2) which has a value of 0.796 with p or significance 0.000 < 0.050 with the contribution of parenting and gender to independence of 63.4%.